Congress of Neurological Surgeons Systematic Review and Evidence-Based Guideline on the Management of Patients With Myelomeningocele: Whether Persistent Ventriculomegaly Adversely Impacts Neurocognitive Development. Issue 3 (16th August 2019) - Blount, Jeffrey P; Durham, Susan R; Klimo Jr, Paul; Assassi, Nadege; Bauer, David F; Beier, Alexandra D; Flannery, Ann Marie; McClung-Smith, Catherine; Nikas, Dimitrios C; Rehring, Patricia; Tamber, Mandeep S; Tyagi, Rachana; et al.
Abstract: BACKGROUND: Myelomeningocele (MM) is the most common congenital anomaly to affect the nervous system and affects 1500-2000 newborn infants per year in the United States. It is accompanied by symptomatic hydrocephalus in approximately 70%-80% of patients. Different treatment strategies for hydrocephalus characteristically result in different effects on the size of the ventricles. OBJECTIVE: The objective of this systematic review was to determine whether persistent ventricular enlargement adversely impacts neurocognitive development in patients with MM. METHODS: The PubMed National Library of Medicine Medline database and Embase were queried using MeSH headings and keywords relevant to neurocognitive or intellectual development and ventricular size or morphology. Abstracts were reviewed by the authors to identify which studies met strict inclusion criteria. An evidence table was constructed that summarized the included studies and reflected the quality of evidence (Classes I–III) that each represented. A recommendation was made that is based on the quality of the evidence. RESULTS: An initial abstract review utilizing strict inclusion/exclusion criteria yielded 48 studies, 9 of which underwent full-text review. There is limited and conflicting Class III evidence from 2 studies. CONCLUSION: Currently, there is insufficient data to conclude that ventricular size and morphology impact neurocognitive development. The full guideline can be found at https://www.cns.org/guidelines/guidelines-spina-bifida-chapter-5 .